Neuraxial anesthesia for a laboring patient with hereditary spastic paraplegia: A case report - Joshua Falescky; Madina Gerasimov; Judith Aronsohn; Gregory Palleschi (Wolters Kluwer Medknow Publications, 2022)
Hereditary spastic paraplegia (HSP) is a rare, inherited condition affecting the corticospinal tract, typically characterized by bilateral lower extremity weakness and stiffness. HSP presents challenges to anesthetic management, particularly in the obstetric population due to the paucity of existing recommendations in the literature. Although case reports exist regarding the successful use of general and neuraxial anesthesia for cesarean section, none currently exist with regard to labor analgesia. Here, we report the use of labor epidural anesthesia in a 29-year-old woman with HSP. She delivered via cesarean delivery after laboring for 27 h with an epidural catheter in place. The patient tolerated epidural placement well with no adverse neurologic sequelae. The utilization of neuraxial techniques avoids the risks associated with airway manipulation in a parturient and obviates the need for the use of muscle relaxants in the setting of upper motor neuron disease. Epidural anesthesia appears to be a safe approach to the management of labor and cesarean delivery in a parturient with HSP.